Exploring the Life and Academic Experiences of International Students at the University of Jambi, Indonesia: A Case Study - Saharudin; Handayani, Reli; Harsyah, Ahmad Syauqi; Marzal, Jefri; Putri, Regita Riani (VELES Voices of English Language Education Society, 2024)
The increasing number of international students in Indonesia's higher education sector urges institutions to improve the quality of their services, facilities, and education. The teaching and learning environment is critical, encompassing the effectiveness of instructional methods, classroom interactions, and the academic support systems provided by the university. Additionally, their socio-experiences, including integration into the campus community and interactions with peers, play a crucial role in their overall well-being and academic success. This study aims to explore the life and academic experiences of international students in undergraduate International Programs at the University of Jambi in Indonesia. This research employed a mixed-method approach, combining a questionnaire adapted from the Strategy Inventory for Language Learning (SILL) and in-depth interviews, with a total of 13 international students from international classrooms participating in the study. The research highlights significant challenges for international students at the University of Jambi, including inadequate classroom and laboratory facilities, poor lighting, and insufficient resources, particularly in Animal Sciences and Agriculture. Language barriers due to Indonesian being the primary medium of instruction further hinder learning. Students express high dissatisfaction with services such as insurance, health facilities, extracurricular activities, and counseling, though library services are well-regarded. Recommendations include adopting English for instruction, providing bilingual training for lecturers, and improving infrastructure and student services to enhance the overall academic experience for international students